Vitamin E supplements in asthma: a parallel group randomised placebo controlled trial. Issue 8 (28th July 2004) - Pearson, P J K; Lewis, S A; Britton, J; Fogarty, A
Abstract : Background: Increased dietary vitamin E intake is associated with a reduced incidence of asthma, and combinations of antioxidant supplements including vitamin E are effective in reducing ozone induced bronchoconstriction. A study was undertaken to investigate the effect of supplementation with vitamin E for 6 weeks on bronchial hyperresponsiveness in atopic adults with asthma. Methods: 72 participants from a clinical trial register of adults with asthma were randomised to receive 500 mg natural vitamin E or matched placebo for 6 weeks in a placebo controlled, double blind parallel group clinical trial. Inclusion criteria included age 18–60 years, maintenance treatment of at least one dose of inhaled corticosteroid per day, a positive skin prick test to one of three common allergens, and bronchial hyperresponsiveness to methacholine (defined as a dose provoking a 20% fall in forced expiratory volume in 1 second (FEV1 ) (PD20 ) of 12.25 μmol). Secondary outcomes were FEV1, forced vital capacity, mean morning and evening peak flow, symptom scores, bronchodilator use, and serum immunoglobulin E levels. Results: In the primary intention to treat analysis the change in PD20 was similar in the vitamin E and placebo groups with a mean difference of +0.25 doubling doses of methacholine (95% confidence interval −0.67 to +1.16 greater with vitamin E). There was no effect of vitamin E supplementation on any other measure of asthma control, either in the intention to treat or per protocol analysis. There was also no effect of vitamin E supplementation on serum immunoglobulin levels. Conclusion: Dietary supplementation with vitamin E adds no benefit to current standard treatment in adults with mild to moderate asthma.